Analisis Peran Badan Permusyawaratan Desa (BPD) dalam Mengoptimalkan Pengelolaan Pembangunan Desa Di Kabupaten Mamasa - Syamsu Alam (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
This research is explanatory using a qualitative approach with descriptive type. The research location was chosen purposively by considering focusing on local actors in the village. The number of informants is 25 people. Data retrieval is done with Questionnaire, Focus Group Discussion and observation. The results show that the role and performance of the BPD in carrying out government functions is still not optimal, this can be seen as follows 1) Contribution The role of the BPD is still very limited and constrained in preparing village development plans compiled in the Village RPJM with a period of 6 (six) years and Village RKP with a period of 1 (one) year, as well as Village APBD which is the annual village financial planning. The low contribution of the BPD involves the community in planning as a manifestation of democratic, transparent and accountable implementation and making the community the subject of development. The indicator that became the failure of the BPD in empowering the community was the low level of community knowledge about the Village RPJM, Village RKP and Village APBD. The knowledge and skills of BPD members are still limited in dynamizing and triggering the wider community (including the poor and women) to be active in village planning, decision making, implementation of the results of village planning and monitoring of their evaluations. 2) The performance of the BPD in absorbing and channeling people's aspirations which are damaged in the form of a policy stipulated in village regulations is still very weak, it can be seen from the BPD's performance in making a legal product that can protect community units such as village regulations on livestock management , management of village forests, customary institutions that are still alive and customary property.